CREATION OF EFFECTIVE PHOTOCATALITIC SYSTEMS WITH EXPANDED LIGHT SENSITIVITY RANGE - Liubomyra, Odosii; Kropyvnytska, L; Kobasa, Igor; Mikhlyova, M. (Published by the decision of the Academic Council at Drohobych Ivan Franko State Pedagogical University, 2019)
The search for effective photocatalytic systems is in the phase of intensive research which mostly focuses on such urgent human problems as photocatalytic transformation and the storage of solar energy. Solar power belongs to one of the most promising areas of the rapidly developing eco-power industry. In particular, the studies in this area also provide an environmental aspect, which is to preserve the stocks of traditional energy sources, fossil fuels, the consumption of which will lead to the inevitable exhaustion accompanied by pollution of the environment.
Keywords: Photocatalyst; Heterostructure; Sensitizer; Polymethinedye